The Legal Status of Azov Sea and the Kerch Strait: Ukraine v. Russia - Astutik, Zulfiani Ayu; Özaltın, Mert Ahmet (Universitas Muhammadiyah Yogyakarta, 2021)
The Black Sea has been the scene of conflict between coastal states throughout history. Recently, emerging Russia-Ukraine tension continues. The Russian Federal Security Service (